2020
DOI: 10.1186/s12912-020-00486-y
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated nursing care: findings from a qualitative study

Abstract: Background Contrary to Missed Nursing Care, some anecdotal data and sparse evidence has documented the tendency of nurses to anticipate some nursing interventions. However, no study has been conducted to date with the purpose of understanding this phenomenon and its underlying mechanisms and consequences. The aim of this study was to describe the phenomenon of delivering anticipated nursing care, its antecedents and consequences as perceived by nurses. Method A descriptive qualitative study. The Consolidated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…In many studies included in this review, victims' personal characteristics such as gender, age, work experience and educational level, are reported to be risk factors for violence perpetrated by patients or family members. Limited professional experience not underpinned by appropriate communication skills, combined with inability to anticipate patient needs (Bottega & Palese, 2020 ), do not enable to notice the initial signs of aggression and consequently prevent it. Other studies have shown that specific interventions aimed at raising nurses' awareness about risk factors, such as young age and limited experience, are essential in reducing aggressive behaviors in patients and their families (Hill et al, 2015 ; Shi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In many studies included in this review, victims' personal characteristics such as gender, age, work experience and educational level, are reported to be risk factors for violence perpetrated by patients or family members. Limited professional experience not underpinned by appropriate communication skills, combined with inability to anticipate patient needs (Bottega & Palese, 2020 ), do not enable to notice the initial signs of aggression and consequently prevent it. Other studies have shown that specific interventions aimed at raising nurses' awareness about risk factors, such as young age and limited experience, are essential in reducing aggressive behaviors in patients and their families (Hill et al, 2015 ; Shi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anticipated nursing care has been used to prevent missed or delayed care and for time management. [29][30][31] Exemplar nurses utilize anticipation of both nursing care and patient needs to avoid distractions and provide PCC. Anticipation also requires teamwork and proper delegation of tasks.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that attempts to describe ANC, together with its antecedents and consequences, as experienced by students during their clinical rotations. Prior to recent studies (Bottega & Palese, 2020), ANC was reported mainly through anecdotal evidence as an expression of routines, traditions and rituals of nursing practice, and a potential issue of the theory–practice gap (Bourgault & Upvall, 2019; Rytterstrom et al., 2011; Shoghi et al., 2019), mostly from the perspective of nurses. However, the clinical environment permeates nursing education, enabling students to develop skills (Papastavrou et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using face‐to‐face, audio‐recorded interviews performed from July to September 2019. The interview guide was developed according to the open‐ended questions reported in Table 2 and the evidence available on ANC (Bottega & Palese, 2020). A preliminary piloting of the interview guide with one interview was conducted by two researchers (refer authors), and it was subsequently confirmed that no changes were requested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation